Foliar Methyl Jasmonate Application Activates Antioxidant Mechanisms to Counteract Water Deficits and Aluminum Stress in Vaccinium corymbosum L. - Cristina Cáceres; Crystal Cazor-Curilef; Patricio Delgado-Santibañez; Mariana Machado; Mabel Delgado; Alejandra Ribera-Fonseca; Claudio Inostroza-Blancheteau; Leon A. Bravo; Jorge González-Villagra; Adriano Nunes-Nesi; Marjorie Reyes-Díaz (Horticulturae)
Due to climate change, water deficits (WDs) and aluminum (Al) toxicity are increasing, affecting plants, especially crops such as blueberries (Vaccinium corymbosum L.). The application of methyl jasmonate (MeJA) could mitigate these effects. This work aimed to evaluate the effective MeJA dose to overcome oxidative stress provoked by combined WD+Al stress in blueberries. Plants of Al-sensitive (Star) and Al-resistant (Legacy) cultivars were exposed to control (Al at 65 mg/Kg, 80% field capacity), WD+Al (50% field capacity; Al at 1665 mg/Kg), and WD+Al treatment with different foliar MeJA doses (10, 50, and 100 μM) during 7 and 21 days. Data revealed that plants exposed to WD+Al and treated with 50 µM MeJA reduced Al up to 3.2-fold in roots and 2.7-fold in leaves and improved water potential (Ψw) up to 2.5-fold. The sensitive cultivar decreased the relative growth rate under WD+Al, increasing by 1.9-fold with 50 µM MeJA. Under WD+Al stress, all MeJA doses mitigated the decrease in relative water content in Al-resistant cultivars, restoring values like control plants. In the sensitive cultivar, 50 µM MeJA increased photosynthesis (1.5-fold) and stomatal conductance (1.4-fold), without changes in transpiration. Lipid peroxidation decreased (1.2-fold) and increased antioxidant activity (1.8-fold), total phenols (1.6-fold), and superoxide dismutase activity (3.3-fold) under WD+Al and 50 µM-MeJA. It was concluded that the most effective dose to alleviate the WD+Al stress was 50 µM MeJA due to the activation of antioxidants in blueberry plants. Therefore, the MeJA application could be a potential strategy for enhancing the resilience of V. corynbosum exposed to WD+Al stress.